Comparing tort and crime : Learning from across and within legal systems - Dyson, Matthew (Cambridge University Press, 2015)
"The fields of tort and crime have much in common in practice, particularly in how they both try to respond to wrongs and regulate future behaviour. Despite this commonality in fact, fascinating difficulties have hitherto not been resolved about how legal systems co-ordinate (or leave wild) the border between tort and crime. What is the purpose of tort law and criminal law, and how do you tell the difference between them? Do criminal lawyers and civil lawyers reason and argue in the same way? Are the rules on capacity, consent, fault, causation, secondary liability or defences the same in tort as in crime? How do the rules of procedure operate for each area? Are there points of overlap? When, how and why do tort and crime interact? This volume systematically answers these and other questions for eight legal systems: England, France, Germany, Sweden, Spain, Scotland, the Netherlands and Australia"--